Developments in Vaccination for Herpes Simplex Virus - Krishnan, Rohini; Stuart, Patrick M. (Frontiers in Microbiology, 2021)
Herpes Simplex virus (HSV) is an alpha herpes virus, with two subtypes: HSV-1 and HSV-2. HSV is one of the most prevalent sexually transmitted infections. It is the cause of severe neonatal infections and a leading cause of infectious blindness in the Western world. As of 2016, 13.2% of the global population ages 15-49 were existing with HSV-2 infection, and 66.6% with HSV-1. This high prevalence of disease and the fact that resistance to current therapies is on the rise, makes it imperative to develop and discover new methods of HSV prevention and management. Among the arsenal of therapies/treatments for this virus has been the development of a prophylactic or therapeutic vaccine to prevent the complications of HSV reactivation. Our current understanding of the immune responses involved in latency and reactivation provides a unique challenge to the development of vaccines. There are no approved vaccines currently available for either prophylaxis or therapy. However, there are various promising candidates in the pre-clinical and clinical phases of study. Vaccines are being developed with two broad focuses: preventative and therapeutic, some with a dual use as both immunotherapeutic and prophylactic. Within this article, we will review the current guidelines for the treatment of Herpes Simplex infections, our understanding of the immunological pathways involved, and novel vaccine candidates in development